Enhancing UAV Navigation in Dynamic Environments: A Detailed Integration of Fick's Law Algorithm for Optimal Pathfinding in Complex Terrains - Airlangga, Gregorius (Buletin Ilmiah Sarjana Teknik Elektro, 2023)
In the realm of Unmanned Aerial Vehicles (UAVs), efficient navigation in complex environments is crucial, necessitating advanced pathfinding algorithms. This study introduces the Fick's Law Algorithm (FLA) for UAV path optimization, drawing inspiration from the principles of molecular diffusion, and positions it in the context of existing algorithms such as A* and Dijkstra's. Through a comparative analysis, we highlight FLA's unique approach and advantages in terms of computational efficiency and adaptability to dynamic obstacles. Our experiment, conducted in a simulated three-dimensional space with static and dynamic obstacles, involves an extensive quantitative analysis. FLA's performance is quantified through metrics like path length reduction, computation time, and obstacle avoidance efficacy, demonstrating a marked improvement over traditional methods. The technical foundation of FLA is detailed, emphasizing its iterative adaptation based on a cost function that accounts for path length and obstacle avoidance. The algorithm's rapid convergence towards an optimal solution is evidenced by a significant decrease in the cost function, supported by data from our convergence graph. Visualizations in both 2D and 3D effectively illustrate the UAV’s trajectory, highlighting FLA's efficiency in real-time path correction and obstacle negotiation. Furthermore, we discuss FLA's practical implications, outlining its adaptability in various real-world UAV applications, while also acknowledging its limitations and potential challenges. This exploration extends FLA's relevance beyond theoretical contexts, suggesting its efficacy in real-world scenarios. Looking ahead, future work will not only focus on enhancing FLA's computational efficiency but also on developing specific methodologies for real-world testing. These include adaptive scaling for different UAV models and environments, as well as integration with UAV hardware systems. Our study establishes FLA as a potent tool for autonomous UAV navigation, offering significant contributions to the field of dynamic path optimization.